Clofarabine: a next-generation deoxyadenosine analogue - Bhalla, Amit (International Journal of Basic & Clinical Pharmacology, 2018)
Acute lymphoblastic leukaemia (ALL) is the most common of the paediatric leukaemias. It is estimated that the use of modern combination chemotherapy results in long-term remission in nearly 80% of children diagnosed with ALL. Despite therapy advances, approximately 20% of children with ALL, experience leukaemia relapse. Clofarabine (2-chloro-2’-fluoro-2’-deoxy-9-β-D-arabinofuranosyladenine) is a second-generation nucleoside analogue and is structurally related to fludarabine and cladribine which are widely used in the treatment of lymphoproliferative disorders. Clofarabine exhibits greater affinity to deoxycytidine kinase (dCyd kinase) and prolonged retention in leukaemic blasts compared to fludarabine and cladribine. Clofarabine inhibits both DNA polymerases and ribonucleotide reductase (RNR). This results in impaired DNA synthesis through inhibition of DNA elongation as well as depletion of deoxyribonucleotides. Accumulation of clofarabine triphosphate, in the blasts of patients with refractory leukemia has been demonstrated. Prolonged intracellular half-life of 24 hours for clofarabine triphosphate. Clofarabine is indicated for the treatment of pediatric patients 1 to 21 years old with relapsed or refractory acute lymphoblastic leukemia after at least two prior regimens.